Vodka And Wine Consumption In A Swine Model Of Metabolic Syndrome Alters Insulin Signaling Pathways In The Liver And Skeletal Muscle - Elmadhun, Nassrene Y. (2012)
BACKGROUND: The purpose of this study was to examine the effects of alcohol in the context of metabolic syndrome on insulin signaling pathways in the liver and skeletal muscle. METHODS: Twenty six Yorkshire swine were fed a hypercaloric, high-fat diet for 4 weeks then split into three groups: hypercholesterolemic diet alone (HCC n=9), hypercholesterolemic diet with vodka (HCVOD n=9) and hypercholesterolemic diet with wine (HCW n=8) for 7 weeks. Animals underwent intravenous dextrose challenge prior to euthanasia and tissue collection. RESULTS: HCC, HCVOD and HCW groups had similar blood fasting glucose level, liver function test, and BMI. Thirty and 60 minutes after dextrose infusion, HCVOD and HCW groups had significantly elevated blood glucose compared to HCC. HCW group had significantly elevated insulin compared to HCC. Immunoblotting in skeletal muscle demonstrated that alcohol up-regulates p-IRS1, IRS2, AKT, AMPKα, PPARα, Fox01, and GLUT4. In the liver, HCW had up-regulation of AKT, AMPKα, and GLUT4 compared to HCC. Skeletal muscle immunohistochemistry demonstrated increased sarcolemmal expression of GLUT4 in both alcohol groups compared to HCC. CONCLUSIONS: Moderate alcohol consumption in a swine model of metabolic syndrome worsens glucose metabolism by altering activation of the insulin signaling pathway in the liver and skeletal muscle.